New observations in the fragile X-associated tremor/ataxia syndrome (FXTAS) phenotype - Fraint, Avram; Vittal, Padmaja; Szewka, Aimee; Bernard, Bryan; Berry-Kravis, Elizabeth; Hall, Deborah A. (Frontiers in Genetics, 2014)
Purpose: Fragile X-associated tremor/ataxia syndrome (FXTAS) was originally defined as tremor, ataxia, cognitive decline and parkinsonism in individuals who carry between 55-200 CGG repeats in the promoter region of the fragile X mental retardation 1 (FMR1) gene. This paper describes a series of patients who meet the definition of FXTAS who presented for care between 2009-2014. Methods/Results: Retrospective chart review of patients seen in the FXTAS clinic at Rush University in Chicago. Conclusions: Patients with FXTAS may present with a progressive supranuclear palsy-like phenotype and eye movement abnormalities are common in these patients. Rapid worsening of gait abnormalities in FXTAS may be due to a secondary spinal issue and should be aggressively treated to regain function. Finally, the FXTAS Rating Scale score does not reliably inform the certainty of diagnosis or CGG repeat size in these patients.